2009
DOI: 10.1080/01904160903308127
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Nitrogen and Potassium Requirements of Canola and Wheat for Yield and Grain Quality

Abstract: Grain yield increases (responses) of canola (oilseed rape, Brassica napus L.) and spring wheat (Triticum aestivum L.) to application of nitrogen (N) and potassium (K) fertilizers were compared in the same experiment at eight field sites over three years (2000)(2001)(2002) in southwestern Australia. Four rates of N (0-138 kg N/ha as urea) and four rates of K (0-60 kg K ha −1 as potassium chloride) were applied. Significant grain yield responses to applied N and K occurred for both crop species at all sites of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 29 publications
3
23
0
Order By: Relevance
“…In addition, soil indigenous P and K supplies were similar for these two rotations. It should be noted that the average fertilizer contributions to yield were 19.9% and 14.5% for the RR rotations and 21.2% and 17.8% for the CR rotations, indicating that optimal P and K fertilizations were still essential for achieving high seed yields from oilseed rape production, in agreement with the results of other studies [37,38]. Furthermore, soil P availability decreased when the soil was converted from flooding to drying, owing to the production of large amounts of amorphous iron [39].…”
Section: Seed Yield and Yield Responses To Fertilizer Applicationssupporting
confidence: 82%
“…In addition, soil indigenous P and K supplies were similar for these two rotations. It should be noted that the average fertilizer contributions to yield were 19.9% and 14.5% for the RR rotations and 21.2% and 17.8% for the CR rotations, indicating that optimal P and K fertilizations were still essential for achieving high seed yields from oilseed rape production, in agreement with the results of other studies [37,38]. Furthermore, soil P availability decreased when the soil was converted from flooding to drying, owing to the production of large amounts of amorphous iron [39].…”
Section: Seed Yield and Yield Responses To Fertilizer Applicationssupporting
confidence: 82%
“…Supplemental K fertilizer has been reported to produce a significant increase (4.1%) in the seed oil (Singh et al, 1997). In contrast, some experiments have shown that the oil concentration is not consistently influenced by the K addition (Tang and Guan, 2001;Govahi and Saffari, 2006;Brennan and Bolland, 2009). Even in Khan's study (Khan et al, 2004), the oil concentration decreased with increasing K levels.…”
Section: Effects Of K-fertilizer Application On Yield and Qualitymentioning
confidence: 89%
“…Brennan and Bolland [32] reported 32% higher potassium (K) requirements of oilseed rape than wheat (Triticum aestivum) for the production of maximum seed yield. At the same K application rate, the concentration of K in shoots was greater for rapeseed than for wheat [33].…”
Section: Discussionmentioning
confidence: 99%